EXPLORING JAVA-CHINA FUSION IN INTERIOR DESIGN OF BEAUTY SPA AND WELLNESS SENOPATI - Azka Zukhrufa; Sri Fariyanti Pane; Maitri Widya Mutiara (Gorga : Jurnal Seni Rupa, 2024)
The 2019 Savvy Sleeper study pinpoints Jakarta as a global center grappling with remarkably elevated stress levels, stemming from urban congestion, economic uncertainties, and socio-political challenges. A Regus survey underscores a substantial 64? Surge in stress levels in Indonesia, posing significant risks to both  physical and mental health. In response, urban residents increasingly turn to healing activities, with spas emerging as vital contributors. Prasetyo et al.’s (2022) research emphasizes the favorable impact of spa experiences on stress reduction and overall well-being, stressing the need for thoughtfully designed spa facilities. The efficacy of spa experiences pivots on interior design, shaping ambiance and elevating relaxation. Recent studies underscore the importance of infusing elements of nature and cultural aesthetics into spa design to create a serene atmosphere. The fusion of Javanese and Chinese design elements, denoted as "Java-China design," presents a captivating aesthetic embraced in modern luxury interior design, embodying cultural exchange and synthesis. This essay probes the intricate interplay between Javanese and Chinese design elements in interior design, emphasizing themes of tradition, innovation, cultural identity, and globalization. Drawing inspiration from Rosemary Killmer's approach, the methodology for shaping the Java-China Fusion interior design at Yu Rirakkusu Beauty Spa ensures a thorough and effective design strategy. Dubbed Omah TuiNa, this design seamlessly melds Javanese elements with modern luxury aesthetics, promising guests a rejuvenating experience that extends beyond mere architectural confines. Positioned as a scholarly discourse, Omah TuiNa delves into the convergence of cultural narratives and the enduring quest for wellness, aiming to provide guests with a retreat-like experience within the urban landscape.